Factor completely, then place the factors in the proper location on the grid. 3x2 + 2xy - y2
3x^2 + 2xy - y^2 = (3x - y)(x + y)
s
Question
Updated 7/8/2014 1:44:48 PM
Rating
8
3x^2 + 2xy - y^2 = (3x - y)(x + y)
Confirmed by yumdrea [7/8/2014 1:51:10 PM]

Questions asked by the same visitor
Solve the following equation, answer as a reduced, mixed number. Then place the correct number in the box provided. 4(3 - 2x) = 15 User: 8(1 - 5x) = 13
Weegy: x=-1/8 User: 9(x - 6) = 8(x + 6) Weegy: 9/10 - 1/2 =0,4 User: 15(2 - x) = 13(3 - x) User: Solve the following equation, answer as a reduced, mixed number. Then place the correct number in the box provided. 4(7x - 1) = 3(2x + 1) - 4(x + 6) Weegy: x=0 (More)
Question
Updated 5/27/2014 9:39:37 AM
4(3 - 2x) = 15
12 - 8x = 15
-8x = 15 - 12
-8x = 3
x = -3/8
Confirmed by andrewpallarca [5/27/2014 9:39:53 AM]
8(1 - 5x) = 13
8 - 40x = 13
-40x = 13 - 8
-40x = 5
x = -5/40 = -1/8
Confirmed by andrewpallarca [5/27/2014 9:40:08 AM]
4(7x - 1) = 3(2x + 1) - 4(x + 6)
28x - 4 = 6x + 3 - 4x - 24
28x - 4 = 2x - 21
28x - 2x = 4 - 21
26x = -17
x = -17/26
Confirmed by andrewpallarca [5/27/2014 9:40:27 AM]
Solve for the indicated variable. P = 3r + 2s; for s P = 3r + 2s; for s
Weegy: The answer is s = P/6r User: Solve for the indicated variable. C = 2r; for r (More)
Question
Updated 7/5/2014 9:49:50 AM
P = 3r + 2s;
2s = P - 3r
s = (P - 3r)/2
Confirmed by yumdrea [7/5/2014 10:01:19 AM]
C = 2r
r = C/2
Confirmed by yumdrea [7/5/2014 10:01:19 AM]
Solve |3 - x| = 8
Weegy: x = 9 User: Solve the following inequality. Then place the correct number in the box provided. 3x Weegy: Here's the solution:3x - 5 User: 3(2x - 4) = 4(x + 1) Weegy: 12x - 20 = 14x + 21, -41 = 2x, x = -41/2, x = -20.5 (More)
Question
Updated 7/4/2018 2:03:27 PM
|3 - x| = 8

3 - x = 8

-x = 8 - 3

-x = 5

x = -5

-(3 - x) = 8

-3 + x = 8

x = 8 + 3

x = 11

Solution : x = -5 or x = 11
3x < 18

x < 18/3

x < 6
3(2x - 4) = 4(x + 1)

6x - 12 = 4x + 4

6x - 4x = 4 + 12

2x = 16

x = 16/2

x = 8
Factor completely 3x2 + 2xy - y2
Question
Updated 7/15/2014 11:00:17 AM
3x^2 + 2xy - y^2 = (3x - y)(x + y)
Confirmed by sujaysen [7/15/2014 1:55:01 PM], Rated good by sujaysen
32,783,939
Popular Conversations
Correct the sentence by selecting the proper pronoun usage. None of ...
Weegy: The coach chose us girls and him to attend the track meet. The sentence is correct as is. User: Correct the ...
In the time of butterflies which character can be described as ...
Weegy: The elements of health, physical, mental/emotional/spiritual, and social are interconnected and should be kept ...
A galaxy that has a shape similar to a football is a(n) ____ galaxy. ...
Weegy: A galaxy that has a shape similar to a football is an irregular galaxy.
In Asia, the Cold war led to
Potential source of radioactive material can be located where?
Weegy: Potential sources of radioactive material can be located in Hospitals, Cancer treatment facilities, University ...
*
Get answers from Weegy and a team of really smart live experts.
S
L
P
1
L
Points 281 [Total 6914] Ratings 2 Comments 261 Invitations 0 Offline
S
L
1
Points 175 [Total 1289] Ratings 0 Comments 175 Invitations 0 Offline
S
L
L
1
P
1
L
P
Points 145 [Total 10465] Ratings 3 Comments 115 Invitations 0 Online
S
L
P
R
Points 134 [Total 2470] Ratings 0 Comments 134 Invitations 0 Offline
S
Points 42 [Total 43] Ratings 0 Comments 42 Invitations 0 Offline
S
L
R
P
Points 30 [Total 2195] Ratings 0 Comments 30 Invitations 0 Offline
S
L
1
1
1
1
1
1
1
1
1
1
1
Points 20 [Total 2350] Ratings 2 Comments 0 Invitations 0 Offline
S
Points 20 [Total 83] Ratings 2 Comments 0 Invitations 0 Offline
S
L
Points 20 [Total 143] Ratings 2 Comments 0 Invitations 0 Offline
S
Points 13 [Total 13] Ratings 0 Comments 13 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.